1989
DOI: 10.1104/pp.90.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the Kinetic Parameters of NADP-Malic Enzyme from a C4Flaveria (Asteraceae) Species

Abstract: We have used the pH variation in the kinetic parameters with respect to malate of NADP-malic enzyme purified from the C4 species, Flaveria trinervia, to compare the pK values of its functional groups with those for the pigeon liver NADP-malic enzyme (Ml Schimerlik, WW Cleland [1977] Biochemistry 16: 576-583) and the plant NAD-malic enzyme (KO Willeford, RT Wedding ] Plant Physiol 84: 1084-1087. Like the other enzymes, the C4 enzyme has a group with a pK of about 6.0 (6.6 for the C4 enzyme), as indicated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Previous studies with NADP-dependent malate dehydrogenase (decarboxylating) from C4 plants showed that structural [7,8] and kinetic [8,12] properties ofthe protein are different depending on the conditions in the medium, with pH being an important effector of this. The results shown here on inhibition by NaCl and other salts suggest that ionic strength is also an important component in the determination of malate dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with NADP-dependent malate dehydrogenase (decarboxylating) from C4 plants showed that structural [7,8] and kinetic [8,12] properties ofthe protein are different depending on the conditions in the medium, with pH being an important effector of this. The results shown here on inhibition by NaCl and other salts suggest that ionic strength is also an important component in the determination of malate dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the extent of inhibition was dependent on the size of the analogues (2 to 4-carbons), the presence of two carboxyl groups along with a 2-hydroxyl or 2-keto moiety important for binding of the substrate analogue to the enzyme. In a study performed with the enzyme from Flaveria trinervia , the presence of a group with a low p K value (6 to 6.6), probably an H residue, was responsible for the binding of the 2-hydroxyl of malate and transfer of the hydride to form the intermediate oxaloacetate [ 41 ]. These results suggest that the extent of inhibition was dependent on the size of the analogues (2 to 3-carbons), the presence of two carboxyl groups along with a 2-hydroxyl or 2-keto moiety important for binding of the substrate analogue to the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Since the pH optimum for the oxaloacetate decarboxylation and Lmalate oxidative decarboxylation reactions are different, the existence of an enzyme residue with pK 5.4-6.0 was proposed. Like the pigeon liver malic enzyme, the C4 NADP-ME has a group, probably a histidyl residue, with a pK of about 5.9-6.6 which binds to malate and facilitates subsequent catalysis (Holaday and Lowder 1989). Therefore, we can conclude that this group must be protonated for oxaloacetate decarboxylation (pH acid) and tmprotonated for malate oxidative decarboxylation (pH alkaline).…”
Section: Discussionmentioning
confidence: 99%